Annotated record of the detailed examination of Mn deposits from DSDP Leg 64 (Holes 474, 474A, 475, 479, 480, 481A)1982 - Joseph R Curray; David G Moore (PANGAEA, 1982)
The origin and evolution of passive continental margins are of great scientific interest and economic importance. During DSDP Leg 64 the Glomar Challenger drilled at eight sites (474-481) in the Gulf of California region. The Gulf of California presented a singular example of tectonics and sedimentation in a very young ocean, being formed by translation and oblique rifting. The sedimentation of the region is hemipelagic, rapid, and largely dominated by siliceous microfossils.Sites 474, 475, and 476 form a transect from oceanic crust to continental crust at the southern tip of Baja California in order to define passive-margin subsidence during the early post-rifting phase. Sites 477, 478, and 481 investigate of the nature of young ocean crust in the Guaymas Basin, where high accumulation rates are common and variable high heat flow indicates active rifting and hydrothermal activity. Sites 479 and 480, are situated on the Guaymas Basin Slope above the proto-Gulf sequences. Interest focused on the paleoceanography of laminated, homogeneous diatom-rich, anoxic sediments within the zone of low oxygen.
Supplement to: Vacquier, Victor; Simoneit, Bernd R T; Schrader, Hans-Jürgen; Saunders, Andrew D; Rueda-Gaxiola, Jaime; Niemitz, Jeffrey W; Molina-Cruz, Adolfo; Matoba, Y; Lyle, Mitchell W; Kelts, Kerry; Kastner, Miriam; Guerrero-Garcia, Jose; Gieskes, Joris M; Fornari, Daniel J; Einsele, Gerhard; Aubry, Marie-Pierre; Aguayo, J Eduardo; Curray, Joseph R; Moore, David G (1982): Initial Reports of the Deep Sea Drilling Project. U.S. Government Printing Office, LXIV, 507 pp + 1303 pp, https://doi.org/10.2973/dsdp.proc.64.1982